Hubungan antara Konsep Diri dengan Keterampilan Berbicara Bahasa Inggris Mahasiswa UHAMKA - Heni Novita Sari Heni (BULLET : Jurnal Multidisiplin Ilmu, 2022)
There are many obstacles faced by students in speaking English. The factors of confidence and courage become a self-image of students in implementing English speaking skills in the classroom and the surrounding environment. Meanwhile, in assessing English speaking skills, students need to have knowledge of vocabulary, grammar, fluency, accent, and understanding. In this case, students not only need to have a positive self-image, but they also need to continue to improve their knowledge that supports their English speaking skills. The purpose of the study was to determine whether there was a relationship between self-concept and English speaking skills of UHAMKA students. The research method used is a survey method with correlational techniques. The data of this study were limited to 43 students in semester 2A and 2B. The self-concept variable data used a questionnaire in the form of a Likert scale and the speaking skill variable data used a speaking test. Data analysis technique used is correlation analysis technique. The results of data analysis are known r-count = 0.432. From the t-distribution table with n = 43 and at 0.05 probability. Then r-table = 0.294. Because r-count > r-table, then Ho is rejected. The conclusion of this study shows that there is a significant relationship between self-concept and English speaking ability of UHAMKA English Education students in semester 2A and 2B, Transactional Listening/Speaking 2017/2018 course. This research will be used as material for evaluation and input for lectures at the Study Program level. UHAMKA English.